CLINICAL AND LABORATORY FEATURES OF PARVOVIRUS INFECTION IN CHILDREN - E. V. Sharipova; I. V. Babachenko; A. L. Mukomolova (Детские инфекции (Москва))
The article is devoted to the study of clinical symptoms and laboratory changes at parvovirus B19 infection in children during the rise of the incidence of infectious erythema. 44 children ailing with laboratory confirmed parvovirus B19 infection aging from 2 months to 14 years were complexly examined. It was established that the disease occurs mainly in boys of preschool and early school age, with a seasonal rise in April and May. General infectious syndrome and syndrome of exanthema dominate the clinical picture. Infectious erythema has benign course.